175k views
3 votes
-x^2 = -36

Solve the equation using inverse operations. Check your solutions. In you final answer, include all of your work.

User G Huxley
by
4.6k points

1 Answer

2 votes

Answer:

x = ±6

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra II

  • Extraneous solutions and multiple answers/roots

Explanation:

Step 1: Define

-x² = -36

Step 2: Solve for x

  1. Divide -1 on both sides: x² = 36
  2. Square root both sides: x = ±6

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute in -6: -(-6)² = -36
  2. Exponents: -(36) = -36
  3. Multiply: -36 = -36
  1. Substitute in 6: -(6)² = -36
  2. Exponents: -(36) = -36
  3. Multiply: -36 = -36

Here we see that both -6 and 6 do indeed work as solutions.

∴ x = ±6 are both solutions to the equation.

User Tim Hunter
by
4.8k points